Literary Tourism on Teaching English Drama Appreciation with a Model Project Based Learning: A Play Performance `Sangkuriang, the Legend of Tangkuban Parahu` - Sulistyorini, Haryati (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This paper entitled, âLiterary Tourism on Teaching English Drama Appreciation with a Model Project Based Learning, a Play Performance, âSangkuriang, the Legend of Tangkuban Parahuâ has a purpose for learners and teachers in literature to give an assumption that literary criticism could be done not only by using reception theory but also used another model in teaching like Project Based Learning. The Project Based Learning in English Drama Appreciation with a play performance of Sangkuriang also has a main purpose to introduce and promote the tourism object of Tangkuban Perahu as the popular tourism object in Indonesia especially in West of Java. This is usually called by travelling literature which also has a function to promote and popular the tourism object. Descriptive qualitative is used to describe the data which is acquired in the project based learning. The result shows that teaching learning in English Drama Appreciation which is done by the project based learning is able to give students in the interpretation on a literary work in a play perform like Sangkuriang.